2006
DOI: 10.1118/1.2179167
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional ionization chamber arrays for IMRT plan verification

Abstract: In this paper we describe a concept for dosimetric treatment plan verification using two-dimensional ionization chamber arrays. Two different versions of the 2D-ARRAY (PTW-Freiburg, Germany) will be presented, a matrix of 16 x 16 chambers (chamber cross section 8 mm x 8 mm; the distance between chamber centers, 16 mm) and a matrix of 27 x 27 chambers (chamber cross section 5 mm x 5 mm; the distance between chamber centers is 10 mm). The two-dimensional response function of a single chamber is experimentally de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
161
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(169 citation statements)
references
References 29 publications
2
161
0
6
Order By: Relevance
“…According to several other studies, gamma analysis to detect 1% of DD and 1 mm of DTA is still controversial for the following reasons: (a) dosimetric errors and statistical fluctuations are dominant for the 1%/1mm criterion, and (b) the acceptable level of %GP for the 1%/1mm criterion should differ from those values for the 3%/3mm and 2%/2mm criteria 36 , 37 , 38 . Thus, a careful approach to gamma analysis with the 1%/1mm acceptance criterion should be taken.…”
Section: Discussionmentioning
confidence: 99%
“…According to several other studies, gamma analysis to detect 1% of DD and 1 mm of DTA is still controversial for the following reasons: (a) dosimetric errors and statistical fluctuations are dominant for the 1%/1mm criterion, and (b) the acceptable level of %GP for the 1%/1mm criterion should differ from those values for the 3%/3mm and 2%/2mm criteria 36 , 37 , 38 . Thus, a careful approach to gamma analysis with the 1%/1mm acceptance criterion should be taken.…”
Section: Discussionmentioning
confidence: 99%
“…However, another problem of MatriXX is its spatial resolution. Poppe et al (16) and Herzen et al (17) suggested a convolution correction method that considers the response function of each detector. This method might enhance the verification results for dose distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Since certain measurement tasks, such as acquiring percent depth‐dose curves or the localization scan at the beginning of a CT examination, are done with a stationary X‐ray tube, these detectors can still be used. General physical properties of the 2D‐Array seven29 have been investigated and described by Poppe et al 29 , 30 , 31 …”
Section: Methodsmentioning
confidence: 99%